Bone health in urban midlife Malaysian women: risk factors and prevention - P.S, Lim; F.B, Ong; N., Adeeb; S.S, Seri; M.Y, Noor Aini; K, Shamsuddin; N, Hapizah; A.L, Mohamed; Awang, Mokhtar; H.W.H, Wan (Springer, 2005)
The aim of this study was to identify risk factors associated with osteoporosis in urban midlife Malaysian women and to assess the effectiveness of lifestyle intervention in bone loss prevention with hormone replacement therapy (HRT) as a positive control. A total of 514 disease-free, uterus-intact, non-HRT-using women aged 45 years and older were recruited into the study. After initial bone mineral density (BMD) assessments, they were randomized into three groups: GI (control), G2 (lifestyle intervention), and G3 (lifestyle intervention with HRT). The study group was composed of 67.5% Chinese, 27.8% Malay, and 4.2% Indians with a mean age of 51.07+/-5.28 years. Two-fifths were postmenopausal, and the prevalence of osteoporosis was 24.1%, seen predominantly at the hip. Postmenopausal women had significantly lower mean BMD and a higher incidence of osteoporosis compared with the premenopausal women, 42.1% vs. 11.1% (p<0.0005). A lower incidence of osteoporosis was found in women who took calcium supplementation regularly as opposed to those who do not, 18.7% vs. 29.3% (p=0.036). Age and a greater postmenopausal duration showed a significant negative association with BMD, whereas higher family income, weight, body mass index, and waist and hip circumference were positively correlated. After 18-20 months, the effect of intervention was assessed based on BMD values of 279 women at baseline and after intervention. Lifestyle intervention alone was effective in premenopausal women, preventing over 90% of spinal bone loss compared with the controls, who lost 11.6% (0.046 g/cm2) bone mass with similar losses of hip bone, 2.0% (0.026 g/cm2) vs. 1.5% (0.020 g/cm2). Premenopausal women on HRT also showed a substantial decrease in spine and hip BMD, 18.6% (0.081 g/cm2) and 9.0% (0.122 g/cm2), respectively. The lifestyle intervention program retarded postmenopausal bone loss by 21% and 37% compared with controls, who lost 9.6% (0.141 g/cm2) and 6.0% (0.138 g/cm2) bone mass at the spine and hip. In comparison, lifestyle intervention with HRT increased postmenopausal BMD by 12.7% (0.216 g/cm2) at the spine and 1.9% (0.042 g/cm2) at the hip. The changes in hip BMD were influenced by current age, ethnicity, and income, while intervention had the strongest effect on spine BMD changes. In conclusion, lifestyle intervention prevented spinal bone loss in premenopausal women and retarded postmenopausal spine and hip bone loss compared with controls. The benefits of physical activity on spine and hip BMD highlight its potential as a safe and cost-effective alternative to HRT, which is not advocated because of its potential adverse effects.